Insulin degludec does not increase antibody formation versus insulin glargine: an evaluation of phase IIIa trials. Issue 7 (8th February 2016) - Vora, J.; Seufert, J.; Solberg, H.; Kinduryte, O.; Johansen, T.; Hollander, P.
Abstract : We examined insulin antibody formation in patients with type 1 (T1D) or type 2 diabetes (T2D) treated with once‐daily insulin degludec (IDeg) or insulin glargine (IGlar) to evaluate the impact of antibody formation on efficacy and safety. Insulin antibodies were measured using subtraction radioimmunoassays in six phase IIIa clinical trials using IDeg (n = 2250) and IGlar (n = 1184). Spearman's correlation coefficient was used to evaluate associations between cross‐reacting antibodies and change from baseline glycated haemoglobin (HbA1c) and insulin dose. IDeg‐ and IGlar‐specific antibodies remained low [<1% bound/total radioactivity (B/T)] and with low levels of antibodies cross‐reacting with human insulin in patients with T1D (<20% B/T) and T2D (<6% B/T). Spearman's correlation coefficients between insulin antibody levels and change in HbA1c or insulin dose were low in both treatment groups. No clinically meaningful differences in adverse event (AE) rates were observed in patients with >10% B/T or without an absolute increase in antibodies cross‐reacting with human insulin. IDeg treatment resulted in few immunogenic responses in patients with T1D and T2D; antibody formation was not associated with change in HbA1c, insulin dose or rates of AEs.